Using polymer electrolyte membranes as media to culture fractals: A simulation study - Amir, S.; Mohamed, N.S.; Hashim Ali, S.A. (2009)
In the authors' laboratory, fern-like fractals have been cultured in polymer electrolyte membranes of polyethylene oxide (PEO) doped with ammonium iodide (N~I). The simulation study was then carried out utilizing the Diffusion Limited Aggregation COLA) based on random motion of aggregating particles modelling technique. The fractal dimension values and the forms of the simulated fractals are comparable to those observed in the PEO polymer membranes. These indicate that the simulation using the DLA model done in this study has resulted outputs that are in abidance with the original fractals cultured in the polymer membranes.